The Blood-Brain Barrier in Space: Implications for Space Travelers and for Human Health on Earth - Amselem, Shimon; Eyal, Sara (Frontiers in Drug Delivery, 2022)
Astronauts have flown to space for decades, but the effects of spaceflight on human health have not been fully clarified yet. Several pathologies have only been detected after it has become customary for astronauts to spend months rather than days in space and with the advance of inflight monitoring. Examples include the neuro-ocular spaceflight associated syndrome, changes to the brain’s white matter, and, more recently, altered cerebral blood flow and related hypercoagulability. This review will present spaceflight-induced brain disorders in astronauts and putative contributing factors. It will next present ongoing and upcoming studies of the BBB onboard space platforms. Finally, it will describe how the space environment can be harnessed for improving drug-delivery across the BBB for humans both in space and on Earth.